Perceived Returns to Job Search - Abigail Adams-Prassl; Teodora Boneva; Marta Golin; Christopher Rauh (Institute of Labor Economics (IZA), 2022)
In this paper we provide the first evidence on workers' perceptions of the returns to job search effort. The perceived job finding probability is nearly linear in hours searched and only slightly concave for most respondents. While workers are over-optimistic about the probability of receiving a job offer conditional on any search, they perceive the marginal return to additional search hours as positive but comparably low. Job seekers receiving an offer update their perceived returns upwards, while others' beliefs regress towards the direction of the mean. We find little evidence that the novel aspects of the pandemic recession have fundamentally changed workers' motivations for job search: that an existing job is expected to end or has unsatisfactory pay are the primary motives for on-the-job search. On the contrary, workers' ability to do their tasks from home is not a strong predictor of job search nor a significant motive for switching occupations.
Keywords: J62; J64; 330; job search; perceived returns; working from home; COVID-19; subjective beliefs; reservation wage